Analisis Pengelolaan Hutan Adat Pasca Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 - Basyar, Taufik Qul; Arfa'i, Arfa'i; Iswandi, Iswandi (Universitas Jambi, Fakultas Hukum, 2024)
Abstract After the issuance of the Constitutional Court's decision Number 35/PUU-X/2012, it had an impact on forest regulation in Indonesia, especially customary forests. The regulation in question is that customary law communities are recognized and protected as legal subjects and their traditional rights. In fact, this form of recognition is found in various government activities, especially activities related to the existence of customary law communities, including the rights of indigenous peoples in the use of natural resources in terms of forest management to obtain optimal benefits from forests and forest areas for the welfare of the community. In the context of the management and utilization of natural resources by indigenous peoples, it is inseparable from the role of the state that regulates the management. Therefore, this study discusses the regulation of customary forest management by the state, especially after the decision of the Constitutional Court Number 35/PUU-X/2012. Keywords: Rights In Management, Customary Forest, Constitutional Court Decision Number 35/PUU-X/2012. Abstrak Pasca dikeluarkanya putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 memberikan dampak terhadap pengaturan hutan di Indonesia terkhusus hutan adat. Pengaturan yang dimaksud adalah bahwa masyarakat hukum adat diakui dan dilindungi sebagai subjek hukum dan hak-hak tradisionilnya. Secara faktual, wujud pengakuan tersebut ditemukan dalam berbagai kegiatan pemerintahan terutama aktivitas yang berkaitan dengan keberadaan masyarakat hukum adat, termasuk hak masyarakat hukum adat dalam pemanfaatan sumber daya alam dalam hal pengelolaan hutan untuk memperoleh manfaat yang optimal dari hutan dan kawasan hutan bagi kesejahteraan masyarakat. Dalam konteks pengeloaan dan pemanfaatan sumber daya alam oleh masyarakat hukum adat tidak terlepas dari peran negara yang mengatur pengelolaan tersebut. Maka dari itu, pada penelitian ini membahas mengenai pengaturan pengelolaan hutan adat oleh negara, khususnya pasca putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012. Kata kunci: Pengelolaan, Hutan Adat, Konsep Pengakuan, Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012.